IMPRESI MOTIVASI MATERIL DAN NON MATERIL PEGAWAI TERHADAP KEPUASAN KERJA PEGAWAI DINAS PENDAPATAN DAERAH KOTA BANDAR LAMPUNG DI MASA NEW NORMAL PADEMI COVID 19 - Muhammad Junaidi; Kasmi Kasmi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2022)
During the current covid pandemic, which can be said to be the new normal period, where all people have received vaccine 2, which does not mean that life is going on normally, it is hoped that with conditions like this we can quickly adapt to the environment. Although during a pandemic, public services must continue to run well, public servants are closely related to the internal culture of the organization. The government bureaucracy in the new normal period is generally lacking in supporting efforts to improve public services. If employee morale begins to decline, it will result in the failure of the goals to be achieved, on the contrary, with high morale, these goals can be achieved properly. The condition that occurs in the Regional Revenue Service of Bandar Lampung City is that there is a decrease in work morale. So that the employees of the Bandar Lampung City Regional Revenue Service in carrying out their work are not optimal. The non-optimal performance of civil servants can be seen from the non-achievement of the work targets that have been set. This study aims to determine the effect of material and non-material motivation of employees on job satisfaction of employees of the Regional Revenue Service of Bandar Lampung City. While the analytical tool used is simple linear regression analysis using t test. The results of the quantitative analysis show that material and non-material motivation (X1) has a significant effect on employee job satisfaction (Y). This conclusion is obtained partially, it is known that material and non-material motivation (X1) has a significant effect on employee job satisfaction (Y) at the Regional Revenue Service of Bandar Lampung City. This is shown from the tcount value of the work motivation variable (X1) = 8,707 and the tcount is greater than the t table value of 1,697.